1987
DOI: 10.1159/000163407
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Expression Kinetics of an Endothelial Cell Activation Antigen Present in vivo Only in Acute Inflammatory Tissues

Abstract: Endothelial cell activation by endotoxin (LPS), tumor necrosis factor (TNF), Interleukin-1-α, β (IL-1-α β) and phorbolesters (TPA) results in increased monocyte adhesion. Examination of kinetics of monocyte adhesion shows that the onset of adherence enhancement (AE) is similar in all five agents (about 300% AE at 6 h), while its decrease is delayed in LPS/TNF versus IL-1-α, β /TPA-induced activation (LPS versus IL-1- β:260% versus 60% at 18 h). Monoclonal antibody (4D10), raised against 24 h LPS-stimulated end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

1988
1988
1998
1998

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 17 publications
2
21
0
Order By: Relevance
“…The decrease in ELAM-1, however, depends on the mediator used. With TNFa ELAM-1 remains elevated 30% above the base val ue after 24 h [8]. It has been shown by Hakkert et al [9] that monocyte adherence to stimulated HUVECs (4 h with IL-1P) is reduced only by about 30% by mAbs against ELAM-1.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…The decrease in ELAM-1, however, depends on the mediator used. With TNFa ELAM-1 remains elevated 30% above the base val ue after 24 h [8]. It has been shown by Hakkert et al [9] that monocyte adherence to stimulated HUVECs (4 h with IL-1P) is reduced only by about 30% by mAbs against ELAM-1.…”
Section: Discussionmentioning
confidence: 93%
“…It has been shown by Hakkert et al [9] that monocyte adherence to stimulated HUVECs (4 h with IL-1P) is reduced only by about 30% by mAbs against ELAM-1. This suggests that ELAM-1 does not play an important role in monocyte adherence although Goerdt et al [8] showed a strong increase in monocyte adherence to ELAM-1-expressing HUVECs. Mediation of neutrophilic adhesion seems to be the main role of ELAM-1 since the expression of ELAM-1 correlated with the influx of neutrophilic granulocytes [7].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In contrast to the average continuous endothe lial cell antigenicity, splenic sinusoidal endo thelial cells express Leu-2 [Turner et al, 1986;Buckley et al, 1985;Buckley and Dickson, 1984] and the transferrin receptor OKT 9 [Buckley et al, 1985], and lack HC1 [Posnett et al, 1984;Rutgers et al, 1986;Scully et al, 1988] and B721 [Voland et al, 1987;Scully et al, 1988]; liver sinusoidal endothelial cells express Leu M3 [Turner et al, 1986], 63D3 and 61D3 [Turner et al, 1986;Ugolini et al, 1980] and lack von-Willebrand antigen I and II, HC1 and B721, renal glomerular endothelial cells lack vonWillebrand antigen I and II. HLA-DR anti gens, OKM 5 [Knowles II et al, 1984] and B721, and acute inflammatory endothelial cells in addition express the putative leuko cyte adhesion molecules H4/18 [Pober et al, 1986] and 4D10 [Goerdt et al, 1987] and the C3b receptor To5 [Smiley et al, 1985;Gerdes et al, 1981;Ryan et al, 1981]. Minor differences are seen, e.g.…”
Section: Introductionmentioning
confidence: 99%